Ecological correlates of chimpanzee termite fishing behavior in Mbam & Djerem National Park, Cameroon - Tyler C. Andres‐Bray; Jeffrey Smith; Ian Nichols; Ekwoge E. Abwe; Mary Katherine Gonder (Ecology and Evolution, 2024)
Abstract Chimpanzee insectivory is seasonally variable, with pronounced peaks or set seasonal periods of consumption observed in most chimpanzee communities. This variation is interesting given that chimpanzees invest considerable effort into complex tool‐using behaviors to acquire insect prey. Evidence suggests this seasonal variation is related to insect behavior, but few studies have been done to empirically examine this relationship. In this study, we assessed whether a seasonal pattern of termite fishing by Nigeria‐Cameroon chimpanzees (Pan troglodytes ellioti) in Mbam & Djerem National Park, Cameroon was driven by termite behavior. We measured termite presence and termite foraging activity monthly at seven termite mounds near Ganga Research Station from April 2022 to April 2023. Macroscopic fecal analysis and camera traps placed at each mound demonstrated termite fishing in this community occurred from March to June, with a rare smaller period of termite fishing in October 2021. Average monthly rainfall, average monthly temperature, and average monthly fruit availability were used to examine potential environmental factors that could impact termite fishing seasonality. Termite presence was significantly different between months with and without chimpanzee termite fishing (t‐test, −6.569, p < .001). Termite presence was also significantly associated with average monthly rainfall (ANOVA, F = 13.9, p = .002, R2 = .775). Termites in this region appear to respond to the transition from dry to wet seasons by moving closer to the soil surface. This corresponds with greater chimpanzee termite fishing, suggesting that termite accessibility may be driving seasonal variation in this behavior.